2015
DOI: 10.1111/jog.12877
|View full text |Cite
|
Sign up to set email alerts
|

Association of NR3C1/Glucocorticoid Receptor gene SNP with azoospermia in Japanese men

Abstract: The NR3C1 rs852977 polymorphism is a potential marker for genetic susceptibility to NOA in Japanese men. Further studies are necessary to clarify the association between the NR3C1 polymorphism and alterations of glucocorticoid signaling pathway leading to male infertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…The results pinpoint GRα, i.e., the biologically active splice variant of the GR, which was also readily detected in HTPCs, among others by Western blot. A previous study employed also Western blotting and reported the full length GRα in whole human testes homogenates [1]. In our study, the same antibody was used for both Western blot and immunohistochemistry, and hence, we conclude that GRα is present also in situ.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…The results pinpoint GRα, i.e., the biologically active splice variant of the GR, which was also readily detected in HTPCs, among others by Western blot. A previous study employed also Western blotting and reported the full length GRα in whole human testes homogenates [1]. In our study, the same antibody was used for both Western blot and immunohistochemistry, and hence, we conclude that GRα is present also in situ.…”
Section: Discussionsupporting
confidence: 67%
“…Clearly, we cannot rule out that low levels of other variants, which are described in humans, including the GRβ variant, may also be expressed [29]. Future studies will also have to address the single nucleotide NR3C1 polymorphisms described [1,4].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This gene is an upstream regulator of protamine expression, implicated in male infertility38 . Supporting this idea, a recent study shows that the percentage of azoospermia in humans change as the YBX2 genotype change39 . Besides, in the same chromosome, the gene BPTF (Bromodomain PHD finger transcription factor; from 48.38 to 48.47 Mb) is responsible to regulate and signaling pathways of embryos and embryonic stem cells in early mouse40 .…”
mentioning
confidence: 90%